Hammershøi painter of northern light ; published on the occasion of the exhibition at the Musée Jacquemart-André, Institut de France, March 14, 2019 through July 22, 2019 - Champion, Jean-Loup; Claustrat, Frank 1961-; Curie, Pierre 1960-; Saabye, Marianne 1945- (Rizzoli Electa, 2023)
"Showcasing the best works by the acclaimed Nordic master of light and solitude, this is the first major book on the artist since 1998. The paintings of Vilhelm Hammershøi (1864-1916) have become increasingly popular due their almost contemporary aesthetic. Admired and celebrated during his lifetime, Hammershøi gradually fell into oblivion before being rediscovered in the 1990s. He is now recognized as the iconic painter of Nordic light and solitude"--
"Culturespaces, partager la culture.
Originally published in French as: Hammershøi : le maître de la peinture danoise. Bruxelles : Fonds Mercator, [2019]
Keywords: Hammershøi, Vilhelm / 1864-1916 / Exhibitions / https://isni.org/isni/0000000083854140; Painting, Danish / Exhibitions; Art, Danish / 19th century / Exhibitions; Art, Danish / 20th century / Exhibitions; Domestic space in art / Exhibitions; Hammershøi, Vilhelm / 1864-1916; Exhibition catalogs; Ausstellungskatalog -- Musée Jacquemart-André -- 14.03.2019- 22.07.2019 -- Fontaine-Chaalis